TOTAL QUALITY MANAGEMENT SEBAGAI ALAT BANTU MANAJEMEN UNTUK MENCAPAI OPTIMALISASI - Firman Ardiansyah Ekoanindiyo (Jurnal Ilmiah Dinamika Teknik, 2010)
The problems of optimization is not easy case. To reach for optimization company go all out by is powered resource mathematically, value which wish to be reached for optimizing by company, formulated with value = total revenue - total cost. Manifestly, attainment of optimal value entangle assorted strategy, what not exclusively rely on price and product which shading below/under department marketing of company, but overall of element of company. Total Approach Quality Management one of effort to reach for optimal value by entangling the overall of company element, below/under one vision with. more efficient and effective Activity process, followed by human resource which is have competence with energy and highly of loyalty effort, will yield the make-up of performance which of satisfaction of consumer. Keywords: Total Quality Management, Optimization